Growth performance and feed utilization of keureling fish Tor tambra (Cyprinidae) fed formulated diet supplemented with enhanced probiotic. [version 1; referees: 2 approved] - Muchlisin, Zainal Abidin; Murda, Tanzil; Yulvizar, Cut; Dewiyanti, Irma; Fadli, Nur; Afrido, Fardin; Mohd Nor, Siti-Azizah; Muhammadar, Abdullah A. (F1000Research, 2017)
Background The objective of the present study was to determine the optimum dosage of probiotic in the diet of keureling fish (Tor tambra) fry. Methods Lactobacillus casei from Yakult® was used as a starter, and enhanced with Curcuma xanthorrhiza, Kaempferia galanga and molasses. The mixture was fermented for 7 days prior to use as probiotic in a formulated diet containing 30% crude protein. Four levels of probiotic dosage; 0 ml kg (control), 5 ml kg , 10 ml kg and 15 ml kg were tested in this study. The fish was fed twice a day at 08.00 AM and 06.00 PM at the ration of 5% body weight for 80 days. Results The results showed that growth performance and feed efficiency increased with increasing probiotic dosage in the diet from control (no probiotic) to 10 ml kg of probiotic dosage and then decreased when the dosage was increased up to 15 ml kg . Conclusions The best values for all measured parameters were recorded at the dosage of 10 ml kg . Therefore, it was concluded that the optimum dosage of enhanced probiotic for T. tambra fry was 10 ml kg of feed.